Central Bank Independence and Inflation: Empirical Analysis - Nwambe, Chioma Sylvia (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Many countries have implemented reforms on their Central Banks granting them more independence from political influences. This can be attributed to the recent research in this area which showed that making the Central Banks more independent is a very good means of achieving lower inflation/price stability in a country. Empirical work supporting this theory shows that there is a significant relationship between inflation and Central Bank Independence but not necessary enough to really bring down inflationary problems. Using data for 6 countries over the period of 1997-2011, result supports this theory but it also shows that other control variable needs to be added for better explanation, and also CBI should be part of policies and strategies to help fight and control inflation in these countries and not necessary the only solution as other policies need to be adopted by their Government and Central Banks. Keywords: Central Bank Independence, Inflation, Budget Surplus

ÖZ : Birçok ülkede, Merkez Bankalarını politik baskılardan daha bağımsız hale getirme yolunda reformlar yapılmıştır. Bu reformların sebebi, bu alanda yapılan çalışmaların merkez bankalarının bağımsız hale getirilmelerinin enflasyon/ fıyat istikrarında olumlu katkısının olduğunu göstermesidir. Bu alandaki empirik çalışmalar enflasyon ile Merkez Bankası bağımsızlığı arasında istatiksel olarak önemli bir ilişki olduğunu göstermektedir. Yine de bu ilişki enflasyon sorununu tamamen çözecek büyüklükte olmayabillir. Bu çalışmada da 6 ülkededen 1997 ile 2011 yılları arasındaki veriler kullanılmış, ve panel veri çalışması sonucunda enflasyon ile Merkez Bankası bağımsızlığı arasında ters bir ilişki olduğu gözlemlenmiştir. Anahtar Kelimeler: Merkez Bankası Bağımsızlığı, Enflasyon, Bütçe Açığı/ Fazlalığı, Para Arzı
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2015. Supervisor: Assist. Prof. Dr. Çağay Coşkuner.
Keywords: Economics; Banks and banking Central - Econometric models; Inflation (Finance); Central Bank Independence; Inflation; Budget Surplus